REMOVAL IMPURITIS GARAM DENGAN METODE PERTUKARAN ION SECARA BATCH - Pujiastuti, Caecilia; Ngatilah, Yustina; Sumada, Ketut; Putri, Dinar Ismilla; Laila, Indah Nur (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Salt is one of the community and industrial consumption products that have the main content of sodium chloride (NaCl). The present quality of the salt product contains about 90-93% sodium chloride, and the other is known as an impurities of calcium (Ca), magnesium (Mg), potassium (K) and sulfate (SO4) ions. The presence of these impurities will decrease the quality of the salt product, so a method is needed to decrease the content of impurities in the salt product. One of the methods that can be used to reduce the levels of impurities such as Ca, Mg, K and sulfate (SO4) ions in salt solution is ion exchange method. In this study we studied the effect of cation resin amount (50-150) grams per liter of salt solution and anion solution (150 grams) and contact time (5-25) minutes on removal of Ca, Mg, K and SO4 ions. The study was conducted in a stirred tank with a fixed rotation speed of 200 rpm, and the initial quality of the salt solution contained Ca ions: 0.07%, Mg: 0.09%, K: 0.04% and SO4: 0.4%. Based on the result of the research, the removal of Ca ion: 93.6%,Mg :78.93%, K : 25.00% dan SO4 : 85.47 %at condition of cation resin amount: 150 gram / liter and contact time 25 minutes